2017
DOI: 10.3389/fimmu.2017.01821
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Basal Level Activation of Complement Mannose-Binding Lectin-Associated Serine Protease-3: Kinetic Modeling of Lectin Pathway Activation Provides Possible Mechanism

Abstract: Serine proteases (SPs) are typically synthesized as precursors, termed proenzymes or zymogens, and the fully active form is produced via limited proteolysis by another protease or by autoactivation. The lectin pathway of the complement system is initiated by mannose-binding lectin (MBL)-associated SPs (MASP)-1, and MASP-2, which are known to be present as proenzymes in blood. The third SP of the lectin pathway, MASP-3, was recently shown to be the major activator, and the exclusive “resting blood” activator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…Another conclusion of our studies was that active MASP-3 must be present in the blood, since only the activated form of MASP-3 can convert pro-FD to FD. Later, we provided direct evidence for the extensive basal-level activation of MASP-3 in human blood by an unknown mechanism ( 76 ). Finally, the debate seems to have settled.…”
Section: Cross-talk Between the Ap And The Lpmentioning
confidence: 93%
See 1 more Smart Citation
“…Another conclusion of our studies was that active MASP-3 must be present in the blood, since only the activated form of MASP-3 can convert pro-FD to FD. Later, we provided direct evidence for the extensive basal-level activation of MASP-3 in human blood by an unknown mechanism ( 76 ). Finally, the debate seems to have settled.…”
Section: Cross-talk Between the Ap And The Lpmentioning
confidence: 93%
“…It has also no natural inhibitor in the blood; therefore, control of its activity is probably achieved simply by its very restricted substrate specificity. MASP-3 is present in the blood as the mixture of the proenzymic and the activated forms; moreover, the activated form seems to be the more dominant variant ( 76 ). In this aspect, it also differs from MASP-1 and MASP-2, which are proenzymic.…”
Section: Components Of Ap and Lp As Potential Drug Targetsmentioning
confidence: 99%
“…MASP-1 circulates as an inactive or proenzyme form, and it turns into an active form when the PRM/MASP-1 complexes bind to carbohydrates (2). Recently, Oroszlán et al (14) demonstrated that MASP-3 circulates as an active form in humans and proposed a mechanism for MASP-3 activation by MASP-1. However, it is unknown whether MASP-3 circulates as an active form in the absence of MASP-1 or how MASP-3 is activated in vivo.…”
Section: Masp-3 Circulated As An Active Form Regardless Of the Role Omentioning
confidence: 99%
“…A recent additional breakthrough has been the finding that MASP-3, which is an alternative spliced form of MASP-1/3 gene, is a positive regulator of the AP of the complement system ( 44 ) and MASP-3 exclusively enables FD maturation ( 45 ). It has been shown that both MASP-1 and MASP-2 can activate MASP-3, but MASP-3 in resting human blood is also present in an active form ( 46 ). In vitro , not in vivo studies, have shown that MASP-1 is essential for bacterial LPS but not Zymosan-induced AP activation ( 47 ), indicating that MASP-1 can regulate a specific AP activation mechanism but not the entire AP.…”
Section: Complement System and Its Activationmentioning
confidence: 99%